Sejarah Pengecualian Rahasia Bank Dalam Upaya Pemberantasan Tindak Pidana Korupsi Di Indonesia - Fabriant Fabriant (Jurnal Ilmiah Mandala Education (JIME), 2020)
Bank secrecy is the main principle in the banking business, and one of the elements that can increase public trust is that banks can trust the bank to keep information about their depositing customers secret. There are 2 theories regarding bank secrecy, namely absolute bank secret theory and relative bank secret theory. In Indonesia, bank secrets can be excluded for several purposes, one of which is for the purpose of eradicating corruption. Currently the regulation regarding bank secrecy exeptions, have been stated in act No. 7/1992 concerning Banking as Amended by Act No. 10/1998. These regulations do not just appear, there is a lengthy process and reforms undertaken regarding bank secrecy arrangements in Indonesia. The history of bank secret exceptions in Indonesia is divided into 3 time periods, namely: The period of the old order government, the period of the new order government, and the period of the reformation government. It can be concluded from the three periods that the regulation of bank secret exeptions in an effort to eradicate corruption in Indonesia has been renewed several times, This is done due to increasingly sophisticated crimes so that a regulation regarding the exception of bank secrets is needed which can facilitate law enforcement officers in carrying out their duties.